2010
DOI: 10.1002/chir.20867
|View full text |Cite
|
Sign up to set email alerts
|

Two‐photon absorption circular‐linear dichroism on axial enantiomers

Abstract: We report on the experimental-theoretical analysis of degenerated two-photon absorption circular-linear dichroism (2PA-CLD) in (S)-(-)-1,1'-bi(2-naphthol) and (R)-(+)-1,1'-bi(2-naphthol) dissolved in THF. 2PA-CLD reveals similarities and differences between optical polarization states for the different enantiomers. These results unveil the potential applications of 2PA-CLD for the study and identification of chiral molecules with active and pivotal role in biological systems and the systematic design of chiral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 47 publications
0
32
0
Order By: Relevance
“…The TPA and two-photon circular dichroism (TPCD) spectra of BINOL were reported recently 70,71 for the species dissolved in tetrahydrofuran (THF). The one-and two-photon spectra of both gas-phase and solvated BINOL have also been studied computationally, see Refs.…”
Section: The Tpa Spectrum Of Binolmentioning
confidence: 99%
See 1 more Smart Citation
“…The TPA and two-photon circular dichroism (TPCD) spectra of BINOL were reported recently 70,71 for the species dissolved in tetrahydrofuran (THF). The one-and two-photon spectra of both gas-phase and solvated BINOL have also been studied computationally, see Refs.…”
Section: The Tpa Spectrum Of Binolmentioning
confidence: 99%
“…In Sec. V, we summarize the results of calculations on R-(+)-1,1 -bi(2-naphtol), or BINOL, a system which was recently the subject of a mixed experimental/theoretical study [70][71][72][73] of its two-photon absorption and circular dichroism 74,75 spectra. Section VI contains our conclusions and outlook.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, the phenomenon of circular linear dichroism (ie, the difference in optical response of the sample for circularly polarized and linearly polarized excitations) can be investigated. 62,155,156 This is because of the specific selection rules of the nonlinear process which require that, for a transition be to observable with s-SHGS, the transition dipole moment vector should have a component perpendicular to the surface. 58,62,131,143,157 Otherwise, the transition becomes inactive for SHGS, and consequently, no s-SHG signal can be recorded even if a resonant transition at the given wavelength might be available.…”
Section: Spectroscopic Methods To Analyze Model Heterogeneous Asymmmentioning
confidence: 99%
“…Very recently, Toro et al reported a powerful variation of CD investigation termed circular-linear dichroism (CLD) in which the difference between the response of a sample to circularly polarized light versus linearly polarized light is investigated. 45 More specifically, Toro et al studied CLD in two-photon absorption employing laser pulses of 25 ps duration. It appears conceivable that replacing the ps laser pulses by fs laser pulses and going from TPA to MPI would extend the applicability of this approach.…”
Section: Conclusion / Outlookmentioning
confidence: 99%